Ответ:
Объяснение:
1) (a +2) ² - 16 = (a + 2 + 4)(a + 2 - 4) = (a + 6)(a - 2)
2) 49 - (x + 7x)² =49 - 64x² = (7 - 8x)(7 + 8x)
3) x²(x − 8) + 14x(x − 8) +49(x−8) = (x - 8)(x^2 + 14x + 49) = (x - 8)(x + 7)^2
4) 9 - x² + 2xy - у² = (3 - x + y)(3 + x - y)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
1) (a +2) ² - 16 = (a + 2 + 4)(a + 2 - 4) = (a + 6)(a - 2)
2) 49 - (x + 7x)² =49 - 64x² = (7 - 8x)(7 + 8x)
3) x²(x − 8) + 14x(x − 8) +49(x−8) = (x - 8)(x^2 + 14x + 49) = (x - 8)(x + 7)^2
4) 9 - x² + 2xy - у² = (3 - x + y)(3 + x - y)